Changes in inflammatory bowel disease subtype during follow-up and over time in 44, 302 patients. (2nd January 2019) - Everhov, Åsa H.; Sachs, Michael C.; Malmborg, Petter; Nordenvall, Caroline; Myrelid, Pär; Khalili, Hamed; Elmberg, Maria; Ekbom, Anders; Askling, Johan; Jakobsson, Gustav; Halfvarson, Jonas; Ludvigsson, Jonas F.; et al.
Abstract: Aim: To investigate inflammatory bowel disease (IBD) register-based subtype classifications over a patient's disease course and over time. Methods: We examined International Classification of Diseases coding in patients with ≥2 IBD diagnostic listings in the National Patient Register 2002–2014 ( n = 44, 302). Results: 18% of the patients changed diagnosis (17% of adults, 29% of children) during a median follow-up of 3.8 years. Of visits with diagnoses of Crohn's disease (CD) or ulcerative colitis (UC), 97% were followed by the same diagnosis, whereas 67% of visits with diagnosis IBD-unclassified (IBD-U) were followed by another IBD-U diagnosis. Patients with any diagnostic change changed mostly once (47%) or twice (31%), 39% from UC to CD, 33% from CD to UC and 30% to or from IBD-U. Using a classification algorithm based on the first two diagnoses ('incident classification'), suited for prospective cohort studies, the proportion adult patients with CD, UC, and IBD-U 2002–2014 were 29%, 62%, and 10% (43%, 45%, and 12% in children). A classification model incorporating additional information from surgeries and giving weight to the last 5 years of visits ('prevalent classification'), suited for description of a study population at end of follow-up, classified 31% of adult cases as CD, 58% as UC and 11% as IBD-U (44%, 38%, and 18% in children). Conclusions: IBD subtype changed in 18% during follow-up. The proportion with CD increased and UC decreased from definition at start to end of follow-up. IBD-U was more common in children.